PENGARUH JOB PORTAL DAN PERSEPSI PENCARI KERJA TERHADAP MINAT MELAMAR PEKERJAAN DI KOTA TANGERANG - Eko Sugiyanto; Nur Haris Ependi; Siti Nurmita Hojaindaroh (POLITEKNIK LP3I JAKARTA, 2025)
The purpose of this research is to carry out an analysis and determine the magnitude of the influence of the Job Portal variable and the job seeker's perception variable on the interest variable in applying for a job in Tangerang City. Technological developments are increasingly advanced and growing rapidly, making it easier for job seekers to search for work online by utilizing Job Portals such as JobStreet. In the research that has been carried out, using quantitative methods to test hypotheses through multiple linear regression analysis is carried out in order to know and understand the magnitude of the influence of the independent variables, namely the Job Portal and perceptions of job seekers, on the dependent variable, namely interest in applying for jobs. The data collection process used a questionnaire via Google Form and distributed online to 96 respondents in Jatiuwung District, Tangerang City. From previous research, the research results explain that there is or is a significant and positive influence from the Job Portal variable and the job seeker's perception variable on the interest variable in applying for a job. The regression coefficient for Job Portal is -0.70, indicating that there is a negative influence on the Interest in Applying for a Job variable, while for the job seeker perception variable it is 1.214, indicating that it has a positive influence. Meanwhile, the results of the F Test indicate that the combination of these two variables simultaneously or as a whole influences the variable interest in applying for a job with a calculated F value of 544.749 and a significant level of 0.000. Based on the variables that have been studied, the R Square value is 0.920, indicating that there is 92% variation in interest in applying for jobs. Meanwhile, the remaining 8 percent of the variations are influenced by other components and are not explained or discussed in this research.